A Comparison of the ECERS-R and ECERS-3: Different Aspects of Quality?. Issue 4 (19th May 2019) - Hestenes, Linda L.; Rucker, Lia; Wang, Yudan Chen; Mims, Sharon U.; Hestenes, Stephen E.; Cassidy, Deborah J.
ABSTRACT: Research Findings : The present study provides an initial descriptive comparison of the Early Childhood Environment Rating Scale–Revised (ECERS-R) and the Early Childhood Environment Rating Scale–Third Edition (ECERS-3) in a relatively large sample in 1 state that uses the Environment Rating Scales within its Quality Rating and Improvement System (QRIS). The results indicate significantly lower average scores for the ECERS-3 compared to the ECERS-R in 105 preschool classrooms and different low-scoring items on each scale. The education levels of teachers and teacher–child ratios were not associated with the ECERS-R, but both variables showed significant differences in relation to the ECERS-3. Finally, both measures showed strong test–retest reliability and moderate internal consistency. Practice or Policy : Given the extensive use of the ECERS-R in QRISs, it is beneficial to compare the 2 instruments as many states consider incorporating the new version into existing systems. Decision makers will need to consider the consequences of no teacher interview in relation to a heavier emphasis on observing certain interactions. This shift may lead to differences in the content of technical assistance, moving away from a focus on particular health, safety, and classroom materials toward the use of materials within certain curricular areas.